Unprotected Left Main Percutaneous Coronary Intervention in Acute Coronary Syndromes with Extracorporeal Life Support Backup - Dawid L. Staudacher; Oliver Langner; Paul Biever; Christoph Benk; Manfred Zehender; Christoph Bode; Tobias Wengenmayer (Scientifica)
Background. Left main PCI is superior to coronary bypass surgery in selected patients. Registry data, however, suggest significant early adverse event rates associated with unprotected left main PCI. We aimed to evaluate safety of an extracorporeal life support (ECLS) as backup system during PCI. Methods. We report a registry study of 16 high-risk patients presenting with acute coronary syndromes undergoing unprotected left main PCI with an ECLS backup. Results. Seven patients (43.8%) presented with an acute myocardial infarction while 9 patients (56.3%) had unstable angina. Unprotected left main PCI could be successfully performed in all 16 patients. Mortality or thromboembolic event rates were zero within the index hospital stay. General anesthesia was necessary only in 5 patients (31.3%). Access site bleeding requiring transfusion was encountered in 4 patients (25.0%). Three patients (18.8%) developed access site complications requiring surgical intervention. All patients were ECLS-free after 96 hours. Conclusions. Unprotected left main PCI could be safely and effectively performed after ECLS implantation as backup in acute coronary syndromes in our patient collectively. Vascular access site complications however need to be considered when applying ECLS as backup system.